The effect of temperature on growth and development of peas : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Horticulture at Massey University - Ragan, Paul (Massey University, 1983)
The influence of temperature on the growth and development of the garden pea was studied at Massey University during 1978-79. Cultivars with single and multiple (double and triple) podding characteristics were grown in a greenhouse experiment with high, medium and low temperature treatments, a field experiment with four successive sowings and a climate room with alternating high and low temperature treatments between vegetative and reproductive growth phases. Plant response to temperature was examined using growth analysis and component analysis techniques. High temperature produced a smaller plant with shortened internodes and a delay in pod set. Net assimilation rate was closely linked with final fresh weight yield and harvest index. There was a direct relationship of net assimilation rate and growth duration to yield when net assimilation rate was not limiting; fresh weight yield increased in direct relation to the number of yield components. High temperature effects complicated by flower and pod abortion indicated that the behavior of yield components must be considered along with harvest index as a selection criterion for earliness and high yield in peas. In all cultivars, the number of yield components decreased as temperature increased, particularly the number of pods per node when high temperature occurred during the vegetative phase. High frequency podding cultivars exhibited the highest instability. Net assimilation rate and competition for assimilates between yield components (sinks) determined the number of yield components that were retained. No one component was identified as the main source of variation in pea yield. Positive interactions between components of yield were identified with yield increases when net assimilation rate was nonlimiting and yield decreases when net assimilation rate was limiting. Negative interactions were associated with yield stability. A balance of negative and positive interactions between components of yield combined with a nonlimiting net assimilation rate (assimilate supply) is needed in high yielding pea cultivars.
Keywords: Peas; Effect of temperature on plants